FUZZY COST OVERRUN ANALYSIS MODEL FOR CONSTRUCTION PROJECT (JOURNAL OF ADVANCES IN CHEMISTRY, 2016)
Now a day’s many factors which affect the productivity in construction project. Due to this delay factors time and cost overrun in a project. In this research helps to identify the most important factors that affect the productivity and form a modelling using fuzzy logic. The data’s were collected through questionnaire survey from engineers, contractors and clients worked within the various construction industries. The collected data’s were analyzed using relative importance index (RII) and ranking the factors based on percentage of relative importance and also this paper presents an application of fuzzy logic for developing delay factors causes cost overrun  model using Fuzzy toolbox of MATLAB Program software. The results can facilitate the construction industry to take measures the delay factors causes cost overrun in construction projects.